M-Shaped Auricular Cartilage as Modified Septal Extension Graft: A Study by Three-Dimensional Anthropometric Analysis in Asian Rhinoplasty - Wang, Dawei; Hou, Kai; Zeng, Ning (Aesthetic plastic surgery, 2021)
Background The septal extension graft is one of the most commonly used grafts in Asian tip plasty techniques. However, the septal extension graft usually induces a hard and immobile nasal tip. The purpose of this study was to evaluate the esthetic outcomes of the modified septal extension graft with M-shaped auricular cartilage by three-dimensional anthropometric analysis. Methods A total of 36 patients received augmentation rhinoplasty with M-shaped auricular cartilage as septal extension graft combined with silicone implant. Thirteen measurement items were evaluated using three-dimensional anthropometric techniques, and the preoperative and postoperative results were compared. Results The majority of patients (91.7%) were satisfied with the postoperative nasal shape. No infection, gross absorption, graft exposure, implant exposure, or implant migration was observed. Compared with the preoperative value, the nasal length, nasal height, nasal depth, nasion height, columella width, nasolabial angle, nasofrontal angle, and nasal depth-nasal width index significantly increased. The nasal width, nasal tip width, and nasal index significantly decreased. Conclusion We performed tip plasty with the M-shaped auricular cartilage as modified septal extension graft, achieving a soft and mobile tip with satisfying tip projection in most patients. Level of Evidence IV This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .